Collaborative Governance In Handling Stunting In Pekanbaru City - Faruq Murtadho; Ranggi Ade Febrian; Sri Maulidiah (International Conference On Law And Social Sciences, 2024)
Stunting is a social problem that has a crucial impact due to malnutrition, so it requires appropriate handling efforts. In handling stunting, the Pekanbaru City Government collaborates with various stakeholders in making joint decisions to complete stunting handling. This research aims to analyze collaborative governance in handling stunting in Pekanbaru City. The basic design in descriptive research with a qualitative approach, data sources are obtained from interview techniques, observation and documentation. Meanwhile, to explain the research results using Ansell and Gash's theory with indicators, initial conditions, institutional design, facilitative leadership, and collaboration processes. The research results explain that stunting management in Pekanbaru City is carried out in collaboration between the government, community and private sector and has not been implemented optimally. Because the collaborative process still has an impact on natural resource imbalances, commitment is unclear in handling stunting, which has led to an increase in the number of stunting cases in Pekanbaru City. This is influenced by the main factor of lack of public awareness of health.